Again on Irkutsk Identity - Tkacheva, Marina (project baikal, 2018)
The discussion is focused on identity of Irkutsk. It points out the processes that encourage its formation and analyzes the key problems concerning the ‘Irkutsk style’, wooden architecture, as well as development and realization of new projects for the historical center of Irkutsk.